Ravens Reconsidered: Raiding And Theft Among Tubu-Speakers In Northern Chad. (20th July 2018) - Scheele, Judith
Abstract: From the outside, northern Chad has long been seen as an area of lawlessness, defined primarily by its inhabitants' alleged propensity for raiding and thieving. From the inside, northern Chad indeed appears as an area that thrives on a rhetoric of predation. This, however, is perhaps best understood not in terms of "crime, " but rather as a striving for personal autonomy, as a public denial of reciprocity in a context where notions of bounded moral community and indeed of long-term social strategies of exchange are not much in evidence. Résumé: Le Nord du Tchad a longtemps été considéré par les observateurs extérieurs comme une terre de non droit, définie principalement par le penchant supposé de ses habitants pour les rezzous et le vol. Localement, une certaine rhétorique de la prédation est également mise en avant pour expliquer les relations sociales externes, mais froid même internes, de la zone. Néanmoins, afin de mieux cerner ces pratiques et ces dynamiques historiques, il semble préférable de ne pas les analyser en premier lieu sous leurs aspects « criminels », mais davantage comme le pendant d'une aspiration à l'autonomie personnelle et du déni public de la réciprocité, dans un contexte où les notions de communautés et de stratégies d'échange à long terme ne sont que peu efficientes.